Follow the Way of Heaven for Health Preservation: Dong Zhongshu’s Perspective of Life (International Journal of World Civilizations and Philosophical Studies, 2024)
This study uses the qualitative research method to analyze Dong Zhongshu’s perspective of life based on the way of Heaven, providing reference value for modern nourishment. The theoretical foundation of this study is his philosophy of Heaven. The methodology for this study is essentially a textual research approach. Dong Zhongshu’s primary work, Chunqiu Fanlu, provides insight into his Yin-Yang philosophy. He established unequivocally that Heaven and human are in the same category, with human life being the most valuable. Human should follow the way of Heaven to preserve their health. The principle of Yin-Yang embodies the way of Zhong He. It is a full way of maintaining one’s health. Dong Zhongshu’s philosophy of health preservation is more than just keeping the body healthy; it is also about having a positive attitude toward life and living in accordance with the theory of Heaven and human. A complete appreciation of life’s significance can only be attained by developing a noble and ideal personality and addressing life with benevolence and responsibility. The ultimate goal is to create peace between Heaven and human, body and mind, and societal harmony. It injects a new force into the Confucian thought of health preservation. It also serves as a reference and inspiration for modern health and wellness.